Prolonged and Pervasive Perturbations in the Composition of the Southern Hemisphere Midlatitude Lower Stratosphere From the Australian New Year's Fires. Issue 4 (14th February 2022) - Santee, M. L.; Lambert, A.; Manney, G. L.; Livesey, N. J.; Froidevaux, L.; Neu, J. L.; Schwartz, M. J.; Millán, L. F.; Werner, F.; Read, W. G.; Park, M.; Fuller, R. A.; et al.
Abstract: The 2019/2020 Australian New Year's wildfires injected record amounts of smoke and biomass burning products into the lower stratosphere. The Aura Microwave Limb Sounder (MLS) tracked the evolution of distinct plumes of fire–influenced air as they rapidly spiraled up to the mid–stratosphere. In the months following the fires, smoke spread throughout the Southern Hemisphere (SH) stratosphere. We contrast the evolution of the SH midlatitude lower stratosphere in 2020 with the 17–year MLS record. Long after the coherent plumes dispersed, data from MLS and other satellite instruments show unprecedented persistent and pervasive depletion in HCl (50%–60% below climatology) and enhancements in ClO and ClONO2 that were not transport related; peak anomalies occurred in mid–2020. We conclude that the observed perturbations likely arose from heterogeneous chlorine activation on widespread smoke particles. The sustained chlorine activation was far weaker than in typical winter polar vortices, inducing at most minor changes in ozone. Plain Language Summary: In late December 2019/early January 2020, during the Black Summer fire season in Australia, an intense outbreak of a number of fire–induced and smoke–infused thunderstorms occurred, collectively known as the Australian New Year's event. Multiple plumes of polluted air were rapidly lofted from the surface and deposited in the lower stratosphere (above 14 km altitude). The largest of the plumes of biomass burning pollutants were tracked by the Microwave Limb Sounder (MLS) on NASA's Aura satellite for several months as they circled the globe. In addition to those distinct confined plumes, smoke from the fires permeated the Southern Hemisphere (SH) lower stratosphere. Well after the discrete plumes dispersed, MLS and other satellite instruments observed widespread and long–lasting perturbations in the composition of the SH midlatitude lower stratosphere. In particular, unprecedented depletion in the main stratospheric chlorine reservoir species (HCl) was accompanied by enhancements in another chlorine reservoir (ClONO2 ) as well as the ozone–destroying form of chlorine (ClO), with maximum departures from average measured in mid–2020. These anomalous signatures likely arose from chemical processing on smoke particles. The enhancement in the ozone–destroying form of chlorine, far weaker than that in winter polar regions, had only minor effects on ozone. Key Points: Satellite data show strongly depleted HCl and enhanced ClO and ClONO2 in the southern midlatitude lower stratosphere through much of 2020 The unprecedented midlatitude chlorine repartitioning likely arose from heterogeneous activation on widespread Australian wildfire smoke The sustained midlatitude chlorine activation was far weaker than in typical winter polar vortices, inducing at most minor changes in ozone